Islam and Hegemony of Local Culture - Badrun Badrun (Sunan Kalijaga: International Journal of Islamic Civilization, 2021)
A global world is a paradoxical world, just like a "double-edged sword". On the one hand, globalization offers a variety of ease of life. On the other hand, it carries risks that threaten the existence of human life. It also imposes a universal culture which implies a general view that the presence of culture is always inseparable from humanity and the general acceptance of values, beliefs, orientations, and institutions by mankind around the world. However, the so-called universal culture is nothing but the West because the West, with all its superiority, is most likely to claim itself as the representation of universal civilization. When civilization is fully controlled by the West, there is a psychological burden for Islam. Islam as a force that had been a superpower of the world for approximately 12 centuries might feel uncomfortable to be the underdog. This situation has made Muslims aspire to get out of colonialism and Western hegemony. There are two responses that arise: a strong desire to re-excel in all aspects such as science, technology, politics, economy, military, etc. on the one hand, and deep hatred towards the West one the other hand. It   is this latter which may have spawned terrorism that is being countered by international communities, mainly Western nations.